Analisis Implementasi Realistic Mathematic Education dan Pembelajaran Matematika Berbasis Digital di SMA Pontianak - Egy Abdi; Indri Astuti; Afandi Afandi (Universitas Indraprasta PGRI Jakarta, 2023)
This research was intended for researchers to analyze strategic components in 21st century learning, namely Realitic Mathematics Education (RME) and digital-based mathematics learning which is manifested in the Learning Implementation Plan at SMAN 03 Pontianak and SMA Kristen Immanuel Pontianak. The method used in this research was qualitative. The analysis was carried out using an assessment rubric which the analysis criteria were constructed by referring to the RME indicator and digital-based learning indicators. In general, the implementation of RME in the lesson plans for both SMAN 03 Pontianak and Christian Immanuel Pontianak High School were in the low category, in this case the researchers identified that contextual content that has benefits for students in real life was classified as not well optimized in every aspect of RME-based learning analysis . RPP SMAN 03 Pontianak, it is necessary to optimize the achievement of indicators fulfillment in digital-based learning because the research output on this variable shows the medium category, while the RPP SMAN Kristen Immanuel analysis shows that it only needs special attention on indicators of developing knowledge, skills and attitudes of teachers through the use of technology is in the medium category, while the other indicators are high.